Efektivitas Metode Pembelajaran Peer Teaching Untuk Meningkatkan Aktivitas Dan Hasil Belajar Siswa Pada Mata Pelajaran Pendidikan Agama Islam Di SMA Negeri 22 Palembang - Hayatun Lestari (Program Magister Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2019)
Peer teaching learning method is a way to present material to students by involving students as teachers after being selected by the teacher based on certain criteria. With the peer teaching method, it is expected to be able to improve student learning activities and outcomes. The purpose of this study is to look at the implementation and effectiveness of peer teaching learning methods in improving student activity and learning outcomes in PAI subjects at SMA Negeri 22 Palembang. This type of research is field research using quantitative research approaches and the design used is quasi-experimental. Data collection instruments were carried out by interview, observation, documentation and tests and data analysis using the T test. The sample in this study was class XI IPA 2 (experimental) and XI IPA 5 (control) each of 30 students. From the results of research on the experimental class posttest, which is classified as active, the initial percentage is 39% to 82%, while the initial percentage of learning outcomes is 43% to 87%. The average value of students has also increased from the pretest of 69.78% to 80.17%. After being calculated using the T test, then to be obtained for 14.41 is greater than t table both at the 5% level of 2.02 and 1% of 2.69. Then the hypothesis is accepted. Means between Variable X and Variable Y there is a significant difference in the increase. So the peer teaching learning model can be said as one of the effective learning models to improve the activities and learning outcomes of PAI in SMA Negeri 22 Palembang.